Effects of temperatures on dynamic parameters of Vuilleumier machine with dwell motion based on developed third-order numerical model. (February 2023) - Zhang, Lei; Guan, Jinhuan; Luo, Baojun; Liu, Jingping; Huang, Yuexin; Hofbauer, Peter
Highlights: Developed a third-order model for Hofbauer cycle machine. Model is validated by experiments. Damping coefficient Cd and spring coefficient K are obtained at various conditions. Respective effects of Th, Tw and Tc on Cd and K are also obtained. Analytical solution based on Cd and K has high accuracy in free stroke's prediction. Abstract: Vuilleumier machine with dwell motion provides huge potential for energy savings in residential heating. However, its efficient operation depends on free stroke. In this work, dynamic characteristics of Vuilleumier machine with dwell motion are studied. Firstly, a third-order numerical model based on one-dimensional computational fluid dynamics is developed for Vuilleumier machine with dwell motion. Secondly, experiments on dynamic performances are conducted to validate the model. The comparisons indicate that simulation results match well with experimental results. Thirdly, damping coefficient C d and spring coefficient K are studied at various conditions. Quantitative and qualitative effects of Th, Tw and Tc on Cd and K are analyzed and obtained. The results show that variations of C d and K at given conditions are in the range of 8.71% ∼ 9.38% and 7.78% ∼ 19.54% respectively. Moreover, predicted free strokes based on obtained C d and K have high accuracy with less than 2% error. The results provide reference for design and control of Vuilleumier machine with dwell motion.